SYSTEMATIC LITERATURE REVIEW: THE IMPLEMENTATION OF THE DISCOVERY LEARNING MODEL TO IMPROVE BIOLOGY LEARNING OUTCOMES IN HIGH SCHOOL - Saputra, Rehan; Maharani, Delfiera Aisyafitri (Department of Biology Education, Faculty of Teacher Training and Education, Universitas Wijaya Kusuma Surabaya, 2024)
Education is a crucial aspect in creating high-quality human resources. The appropriate learning model, such as Discovery Learning, plays a vital role in enhancing student learning outcomes, particularly in Biology at the high school level. Discovery Learning emphasizes the process of concept discovery by students through active learning activities, helping them build knowledge independently and meaningfully. This study aims to evaluate the effectiveness of the Discovery Learning model in improving high school biology learning outcomes through a systematic literature review using the PRISMA method. The analysis of seven articles that met the criteria shows that Discovery Learning significantly enhances high school students' biology learning outcomes. These findings highlight the effectiveness of Discovery Learning in deepening students' understanding of biological concepts and increasing their motivation.